Topical Application of Doxycycline Inhibits Th2 Cell Development Mediated by Langerhans Cells and Exerts a Therapeutic Effect on Atopic Dermatitis - Katsuhiko Matsui; Yuki Nojima; Yuka Kajiwara; Kana Busujima; Yuki Mori (Journal of Pharmacy & Pharmaceutical Sciences, 2020)
Background: Langerhans cells (LCs) polarize the immune milieu towards a T helper type (Th) 1 or Th2 immune response. We investigated the effects of selected tetracyclines on Th cells development mediated by LCs, and their implications for the treatment of atopic dermatitis (AD). Methods: Mice were primed with ovalbumin (OVA) peptide-pulsed LCs, which had been treated with each antibiotic, via the hind footpad. After 5 days, the Th1/Th2 cytokine response in the popliteal lymph nodes was investigated by enzyme-linked immunosorbent assay. The expression of cell surface molecules on LCs was investigated using reverse transcriptase polymerase chain reaction. The therapeutic effects of a selected antibiotic on AD-like skin lesions of NC/Nga mice were assessed in terms of the skin severity score, histological changes in the lesioned skin, the serum level of total IgE, and expression of Th1/Th2 cytokines in lymph nodes and skin lesions. Results: Antibiotic-treated, OVA peptide-pulsed LCs inhibited development of Th2 cells but not Th1 cells. This was accompanied by suppression of T-cell immunoglobulin and mucin domain-containing protein (TIM)-4 expression in LCs. Doxycycline had the greatest activity against Staphylococcus aureus strains isolated from skin lesions of patients with AD, and a strong inhibitory effect on Th2 cell development. Doxycycline suppressed the increase in the skin severity score during the acute phase in NC/Nga mice similar to betamethasone. This suppressive effect was associated with a decrease in the serum IgE level and production of Th2 cytokines in auricular lymph node cells and skin lesions. Conclusion: Topical application of doxycycline to AD lesions would act on both superficial S. aureus colonization and epidermal LCs, thus possibly inhibiting the development of Th2 cells in vivo, with benefits for control of acute inflammation in AD.